К проблеме курганов и курганной стратиграфии - Берестнев, С. И. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryS. Berestnev. To the Problem of Burial Mounds and Burial Mounds’ StratigraphyIn the article the matter of burial mound semantics as above burial architecture structures is under the consideration. The structure analysis of the most ancient at Eastern Europe steppe’s burial mound shows that the process of creation them was the reflection of complicated religious ceremony, not rarely prolonged in time. This gives us reason that the burial mounds appear as open sanctuaries, cult center1s which integrated cattlebreeding groupings. Primary burials under artificial mounds may be considered as the acts of symbolic sacrifices to personified nature deities. The roles of sacrifices acted people during their lives directly connected to cults’ performance. Planigraphic, stratigraphic and ritual peculiarities of burials probably reflected internal differentiation of priestly estate.